I am trying to prove that $\|A\|=\sup_{||x||=1}|\langle x,Ax\rangle|$ for some selfadjoint bounded operator A on a Hilbertspace.

Can anyone give me a hint how to prove it.

• We need some more information to be able to help you here. What definition are you given for $\|A\|$ for an arbitrary operator $\|A\|$? What ideas have you had so far, and where do you think you got stuck? Jul 7 '14 at 18:51
• Well $\|A\|:=\sup_{\|x\|=1}\|A x \|$. I tried: $\|A\|^2=\sup \langle Ax,Ax\rangle =\sup \langle x,A^2 x\rangle = \|A^2\|$. So I can conclude that $\|A^2\|=\sup \langle x,A^2 x\rangle$. So by setting $\sqrt{|A|}:=\sqrt{\sqrt{A^2}}$, I have $\| |A| \|=\sup \langle x, |A| x\ \rangle$. Jul 7 '14 at 18:54
• You're assuming what you're trying to prove there. I'll update my answer to expand a bit. Jul 7 '14 at 19:08
• Now I think I don't assume that as $\|A\|^2 = \|A^2\|$ for self-adjoint operators. Jul 7 '14 at 19:09
• Omnomnomnom: You definitely can use the spectral theorem, because you can reduce to a multiplication operator with a real function and the theorem holds for such an operator. More importantly, the same property can be shown to hold for any normal operator, as shown in Theorem 12.25 in the book Functional Analysis by Rudin. Jul 7 '14 at 19:30

It is clear that $|\langle Tx,x\rangle|\leq \|T\|$ for $\|x\|=1$. For the converse, it suffices to show that $|\langle Tx,y\rangle|\leq \alpha$ for all $\|x\|=\|y\|=1$, with $\alpha=\sup\bigl\{|\langle Tx,x\rangle|: \|x\|=1\bigr\}$. We can clearly assume $\langle Tx,y\rangle \in\mathbb R$. Then $$\langle Tx,y\rangle = (\langle T(x+y),x+y\rangle - \langle T(x-y),x-y\rangle)/4.$$ But then $$|\langle Tx,y\rangle|\leq\alpha(\|x+y\|^2+\|x-y\|^2)/4=\alpha,$$ by the parallelogram identity.
• Why does It suffice to work with $|\langle Tx,y\rangle|$? I have been thinking about it and WOL you can suppose that $||T|| = 1$ (dividing by $||T||$ at both sides), but $||T||^2=\sup\bigl\{||Tx||^2 : \|x\|=1\bigr\}=\sup\bigl\{<Tx,Tx> : \|x\|=1\bigr\}$. If I call $y=Tx$ I get something similar to your expression but I don't think this is the correct way... Jul 1 '17 at 15:11
• For $y=Tx/\lVert Tx \rVert$, we have $\lVert Tx \rVert=\langle Tx,y\rangle.$ Jul 1 '17 at 15:17
• @Teodorism To get the first displayed formula, you have to use that $\langle Ty,x\rangle=\langle Tx,y\rangle$, which follows from self-adjointness and the assumption the first value is real. (late answer, but for the benefit of other readers) May 10 '20 at 20:27